Three separated phase's equations regarding nano-encapsulated phase change material/multi-walled carbon nanotube-Fe3O4-water mixture in a porous half-annulus collector with corrugated wall using Buongiorno's model: Brownian and thermophoresis effects - Abu-hamdeh, Nidal H.; Melaibari, Ammar A.; Alquthami, Thamer S.; Khoshaim, Ahmed; Öztop, Hakan Fehmi; Karimipour, Arash (Wiley, 2026)
The multi-phase free convection of nano-encapsulated phase change material (PCM)/multi-walled carbon nanotube (MWCNT)-Fe3O4-water mixture inside an inclined porous half-annulus collector has been simulated using the Buongiorno's mathematical model. To create the buoyancy force, the internal Corrugated and outer cylinder wall are in the high constant hot flux as the hot wall and the constant temperature as the cold wall, respectively. The present study is investigated the effects of Rayleigh number (8 & times; 10(2) <= Ra <= 7 & times; 10(4)), Darcy number (Da = 0.01 and 1), inclined angle (0 <= zeta <= 90), and nanoparticles fraction ratio (0 <= zeta <= 1) on flow pattern, temperature contours, nanoparticles distribution contours, dimensionless distribution of nanoparticles on the walls, and Nusselt number. Results show that the distribution of MWCNT inside the collector and on the walls is more uniform than Fe3O4 nanoparticles. The replacement of MWCNT with PCM is also analyzed to provide the more desired performance.
Keywords: Buongiorno's model; multi-phases; MWCNT; Nano-encapsulated phase change material (NEPCM); porous medium